2013
DOI: 10.1161/jaha.113.000244
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Cardiovascular Health in Young Adult Populations From the United States, Finland, and Australia and Its Association With cIMT: The International Childhood Cardiovascular Cohort Consortium

Abstract: BackgroundGoals for cardiovascular (CV) disease prevention were set by the American Heart Association in 2010 for the concept of CV health. Ideal CV health is defined by 7 CV health metrics: blood pressure, glucose, cholesterol, body mass index, and physical activity on recommended levels; nonsmoking; and a healthy diet. We studied the prevalence of ideal CV health and its associations with ultrasonographically measured carotid intima‐media thickness (cIMT) cross‐sectionally in 5 international populations.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 43 publications
11
61
0
1
Order By: Relevance
“…Previous studies have found the prevalence of ICH to be low or absent in adolescent,22, 38, 39 young adult,40 and adult populations 41. Our findings are consistent with existing literature, and extend these concerning results to a younger population (mean age: 12.8 years; SD 2.7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have found the prevalence of ICH to be low or absent in adolescent,22, 38, 39 young adult,40 and adult populations 41. Our findings are consistent with existing literature, and extend these concerning results to a younger population (mean age: 12.8 years; SD 2.7).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, only 1 participant met the ideal criteria for the healthy diet score. Previous studies have attempted to address this issue by dichotomizing the number of ICH metrics (≤3 or ≥4 ICH metrics),39 creating summary scores for total number of ICH metrics present (maximum of 7),22, 40 or generating a composite score (0, 1, or 2 assigned for poor, intermediate, and ideal cardiovascular health, respectively, for each of the 7 factors) 15. Alternatively, it may be beneficial to consider a continuous ICH metric that captures the dynamic physiological state of cardiovascular health 24, 44, 45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is defined by the presence of 7 ideal health factors that describe whether a person has ideal cardiovascular health and indicate where improvement is needed to attain better health. 1 Substantial evidence demonstrates that the ideal cardiovascular health index is associated with better vascular health 2 and with reductions in cardiovascular morbidity and mortality. 3,4 Childhood and youth are important stages of life because cardiovascular diseases are rooted in early life 5,6 and social January 20, 2015…”
mentioning
confidence: 99%
“…Additionally, the prevalence of the ideal cardiovascular (CV) health metric has been studied in populations around the globe, however it has been mostly focused on country groups that are primarily of caucasian ethnicities, such as Finland, Australia, and the United States. [19] We chose to examine a primarily caucasian population group against a primarily hispanic population group to assess whether there are differences in CV behaviors and risk factors between the two countries and whether the associated trends between behaviors and risk factors is a universal trend or not.…”
Section: Introductionmentioning
confidence: 99%